Appraising the ACCC's Caltex-Mobil decision: An alternative measure of competition based on networks - Bloch, Harry; Wills-Johnson, N. (The Australian National University, 2011)
On 2nd December 2009, the Australian Competition and Consumer Commission (ACCC) announced its intention to oppose the acquisition of Mobil's Australian retails assets by Caltex, based in part on an assessment of the adverse competition effects in some local markets. The proposed merger was subsequently abandoned. The ACCC assessment was based on a standard structural measure of competition, the proportion of petrol stations within each local market that would become controlled by Caltex following such a merger. This paper applies an alternative concept of competition bases on the position of each station within a network. Application of the alternative concept to the Perth market, which was excluded from the ACCC analysis, suggests a greater anti-competitive effect from the Caltex-Mobil merger than indicated by application of the standard structural measure of competition.